Analysis of Textbook use in 4th and 5th Grades of Primary School - Milena B. Ivanuš Grmek (University of Belgrade, Teacher Education Faculty, 2021)
A modern trend in quality textbooks is to stimulate different areas of student development – social, cognitive, moral, and emotional, considering students’ learning specifics. Textbooks are adapted to students if they consider their developmental level, experience and level of understanding; use appropriate language; encourage reading through comprehension, and include illustrations in the text (Marentič Požarnik, 2016). The quality of learning resources that students can also use to learn independently is important. The main purpose of the Slovenian project The Quality of Slovenian Textbooks (KaUč) is to develop textbook quality indicators for practical use in validation and evaluation processes. As part of the KaUč project, an empirical research was conducted on the research sample of 505 students, with its research aim to analyse the use of textbooks and workbooks in 4th and 5th grades of primary school. Based on the performed analyses, we can determine that the use of printed textbooks prevails in all educational subjects. Textbooks are most often used for the first foreign language subject, science and technology, and for social studies.